Cross-Cultural Communication Between Pakpak Simsim and Pakpak Boang - Dewi Dokate Manalu; Syahrul Abidin (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to determine cross-cultural communication between pakpak simsim and pakpak boang, factors of language differences in communication, clan identity factors, cultural customs of pakpak Simsim and pakpak Boang. as well as communication in customs and traditions. Similarities in language or communication are used by both, but what distinguishes them is the dialect as in the mention of the letter "r" in Boang language, it sounds "gh" in the sound of "ghaif" in hijaiyah letters. This study uses descriptive qualitative methods or library research. The data sources used are observation, interviews, primary and secondary data. The theoretical basis used is interaction theory and social identity theory. The informants in this study are traditional leaders and also the people of the Pakpak Simsim and Pakpak Boang tribes. The research conducted, it can be concluded that in the context of cross-cultural communication between Suak Simsim and Suak Boang basically have different dialects in interaction and also differences in language even though they also have some similarities in language, as well as clans